ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN (STUDI EMPIRIS PADA PERUSAHAAN-PERUSAHAAN YANG TERDAFTAR DI BEI TAHUN 2010-2012 - Rahmawati, Siti Hamda; -, Zulbahridar; Lukman, Al Azhar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The company's main goal is to maximize the value of the company. The value of the company is very important because the value of the company reflects the performance of companies that could affect investors' perception of the company. This study aimed to examine the effect of ownership structure consisting of institutional ownership and managerial ownership, dividend policy, debt policy and profitability of the company's value on all companies listed on the Stock Exchange in 2010 until 2012. The enterprise value is calculated by using Tobin's Q Ratio. The population in this study are all companies listed on the Stock Exchange in 2010-2012, where there are 420 companies registered during the study period. The sampling technique used purposive sampling method and obtain the results of 85 companies that meet the criteria of the sample. For the analysis of the data used in this study is multiple regression analysis with the help of computer applications SPSS version 17.0. The results of this study indicate that institutional ownership has no effect on the value of the company with a significance value of 0,939 > 0,05 and the influence of -0.077. For managerial ownership also has no effect on the value of the company with a significance value of 0,451 > 0,05 and the effect of 0,755. For dividend policy has an influence on the value of the company with a significance value of 0,033 < 0,05 and influence of 2,148. For debt policy has an influence on the value of the company with a significance value of 0,012 < 0,05 and effect of -2,232. And to profitability has an influence on the value of company with a significance value of 0,027 < 0,05 and influence of 2,212. This research also obtained the result that the adjusted R Square of 15.2%, which means the value of the company can be explained by 15.2% by institutional ownership, managerial ownership, dividend policy, debt policy and profitability, the rest is influenced by other variables not examined by author.Keywords: Institutional ownership, Managerial ownership, Dividend policy (DPR), Debt Policy (DER), Profitability (ROA), Company Value